The Effect of Pharmacist Counseling on Medication Adherence and Blood Pressure Values in Hypertensive Patients - Sabiti, Farroh Bintang; Fatiha, Chilmia Nurul; Timur, Willi Wahyu; Dewi, Peggy Anastia (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Hypertension is a disease often found in Indonesia. Hypertension can be controlled by compliance with taking medication and a healthy lifestyle. One effort to increase compliance is counseling. Pharmacist counseling can provide patient education and understanding of hypertension therapy while ensuring that patients are taking medication appropriately so as to increase compliance and control blood pressure. The aim of the research was to determine the effect of pharmacist counseling on drug compliance on blood pressure values in hypertensive patients at the Semarang Community Health Center. This research is a pre-experimental study with a One Group Pretest-Posttest design. Data collection was taken in March-April 2019. Blood pressure results were obtained before and after counseling with a value of p = 0.000 (p 0.05). This research can be concluded that pharmacist counseling can influence medication adherence and systolic and diastolic blood pressure values in hypertensive patients at the Semarang Community Health Center